Tinjauan Yuridis Ketentuan Uang Muka Di Bawah Ketentuan Peraturan Menteri Keuangan Dan Otoritas Jasa Keuangan - Ardina Yolanda; Muhammad Ali Hanafiah Selian (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
This thesis aims to determine the application of advances in the provisions of the applicable laws and regulations. Then question, what is the legal consequences of violating the provisions stipulated under the Minister of Finance Regulation Number 43 / PMK.010 / 2012 concerning Advances for Consumer Financing for Motor Vehicles in Financing Companies, and Financial Services Authority Regulation Number 35 / POJK.05 / 2018 Regarding the Operation of Financing Companies. The type of research used in this research is juridical normative by examining library materials or secondary data as the basic material for research by conducting a search of the regulations and literature related to the problem under study. The results of this thesis research show that the Regulation of the Minister of Finance Number 43 / PMK.010 / 2012 concerning Advances for Consumer Financing for Motor Vehicles in Financing Companies and the Regulation of the Financial Services Authority Number 35 / POJK.05 / 2018 concerning Business Operation of Financing Companies do not conflict with prevailing laws and regulations.Keywords: Finance Companies, Minister of Finance Regulation, Financial Services Authority Regulation, Down Payment